Maternal smoking during pregnancy and fetal organ growth: a magnetic resonance imaging study - Anblagan, Devasuda; Jones, Nia W.; Costigan, Carolyn; Parker, Alexander J.J.; Allcock, Kirsty; Aleong, Rosanne; Coyne, Lucy H.; Deshpande, Ruta; Raine-Fenning, Nick; Bugg, George; Roberts, Neil; Pausova, Zdenka; et al. (Public Library of Science, 2013)
Objective: To study whether maternal cigarette smoking during pregnancy is associated with alterations in the growth of fetal lungs, kidneys, liver, brain, and placenta. Design: A case-control study, with operators performing the image analysis blinded. Setting: Study performed on a research-dedicated magnetic resonance imaging (MRI) scanner (1.5 T) with participants recruited from a large teaching hospital in the United Kingdom. Participants: A total of 26 pregnant women (13 current smokers, 13 non smokers) were recruited; 18 women (10 current smokers, 8 nonsmokers) returned for the second scan later in their pregnancy. Methods: Each fetus was scanned with MRI at 22–27 weeks and 33–38 weeks gestational age (GA). Main outcome measures: Images obtained with MRI were used to measure volumes of the fetal brain, kidneys, lungs, liver and overall fetal size, as well as placental volumes. Results: Exposed fetuses showed lower brain volumes, kidney volumes, and total fetal volumes, with this effect being greater at visit 2 than at visit 1 for brain and kidney volumes, and greater at visit 1 than at visit 2 for total fetal volume. Exposed fetuses also demonstrated lower lung volume and placental volume, and this effect was similar at both visits. No difference was found between the exposed and nonexposed fetuses with regards to liver volume. Conclusion: Magnetic resonance imaging has been used to show that maternal smoking is associated with reduced growth of fetal brain, lung and kidney; this effect persists even when the volumes are corrected for maternal education, gestational age, and fetal sex. As expected, the fetuses exposed to maternal smoking are smaller in size. Similarly, placental volumes are smaller in smoking versus nonsmoking pregnant women.